Populism, nativism, and voting behaviour: a global perspective - Macdonald, Helen; Stellenbosch University. Faculty of Arts and Social Sciences. Dept. of Political Science. (Stellenbosch : Stellenbosch University, 2023)
Thesis (DPhil)--Stellenbosch University, 2023.